Treatment advocate tactics to expand access to antiviral therapy for HIV and viral hepatitis C in low‐ to high‐income settings: making sure no one is left behind - Grillon, Céline (J Int AIDS Soc, 2018)
INTRODUCTION: Worldwide, 71 million people are infected with hepatitis C virus (HCV), which, without treatment, can lead to liver failure or hepatocellular carcinoma. HCV co‐infection increases liver‐ and AIDS‐related morbidity and mortality among HIV‐positive people, despite ART. A 12‐week course of HCV direct‐acting antivirals (DAAs) usually cures HCV – regardless of HIV status. However, patents and high prices have created access barriers for people living with HCV, especially people who inject drugs (PWID). Inadequate access to and coverage of harm reduction interventions feed the co‐epidemics of HIV and HCV; as a result, the highest prevalence of HCV is found among PWID, who face additional obstacles to treatment (including stigma, discrimination and other structural barriers). The HIV epidemic occurred during globalization of intellectual property rights, and highlighted the relationship between patents and the high prices that prevent access to medicines. Indian generic manufacturers produced affordable generic HIV treatment, enabling global scale‐up. Unlike HIV, donors have yet to step forward to fund HCV programmes, although DAAs can be mass‐produced at a low and sustainable cost. Unfortunately, although voluntary licensing agreements between originators and generic manufacturers enable low‐income (and some lower‐middle income countries) to buy generic versions of HIV and HCV medicines, most middle‐income countries with large burdens of HCV infection and HIV/HCV co‐infection are excluded from these agreements. Our commentary presents tactics from the HIV experience that treatment advocates can use to expand access to DAAs. DISCUSSION: A number of practical actions can help increase access to DAAs, including new research and development (R&D) paradigms; compassionate use, named‐patient and early access programmes; use of TRIPS flexibilities such as compulsory licences and patent oppositions; and parallel importation via buyers’ clubs. Together, these approaches can increase access to antiviral therapy for people living with HIV and viral hepatitis in low‐, middle‐ and high‐income settings. CONCLUSIONS: The HIV example provides helpful parallels for addressing challenges to expanding access to HCV DAAs. HCV treatment access – and harm reduction – should be massively scaled‐up to meet the needs of PWID, and efforts should be made to tackle stigma and discrimination, and stop criminalization of drug use and possession.